4th AIAA/CEAS Aeroacoustics Conference 1998
DOI: 10.2514/6.1998-2224
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental investigations of airframe noise

Abstract: An extensive numerical and experimental study of airframe noise mechanisms associated with a subsonic high-lift system has been performed at NASA Langley Research Center (LaRC). Investigations involving both steady and unsteady computations and experiments on a small-scale, part-span flap model are presented. Both surface (steady and unsteady pressure measurements, hot films, oil flows, pressure sensitive paint) and offsurface (5 hole-probe, particle-imaged velocimetry, laser velocimetry, laser light sheet mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 11 publications
(7 reference statements)
0
20
0
Order By: Relevance
“…The In particular, one may note the dramatic effectiveness of the porous-tip treatment at locations beyond the trailing edge (figs. [21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The In particular, one may note the dramatic effectiveness of the porous-tip treatment at locations beyond the trailing edge (figs. [21][22].…”
Section: Resultsmentioning
confidence: 99%
“…To construct a time history of length T , the nondimensional loading spectrum, given by Eqn. (1), is sampled at 2 n values separated by dS = D/V n T . Each value, F i , i = 1, 2 n , is assigned a random phase and an inverse Fourier transform is used to generate a time history.…”
Section: Generation Of Loading Time Historymentioning
confidence: 99%
“…The goal of NASA's Advanced Subsonic Technology (AST) Program is a total aircraft noise reduction of 10 EPNdB relative to 1997 levels. 1 Previously, engine noise has been the major source of aircraft noise, but with the introduction of engine noise reduction technologies, it has been found that on approach the airframe noise is comparable with the engine noise and could well exceed it in the future. At take-off the major component of aircraft noise is still the engine noise since the engine is operating at full power.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction D EFINED as the "nonpropulsive noise of an aircraft in flight" in [1], noise produced by airframe components becomes significant during the approach-to-land phase of aircraft operations. Research efforts on identifying and understanding the noise sources associated with the individual airframe components, in particular, high-lift systems, have been undertaken by many researchers [2]. It has been confirmed experimentally in [3][4][5], and analytically by using empirical methods [6], that both leading-edge slats and trailing-edge flap side edges are the most important noise contributors from the high-lift systems to overall noise levels of an aircraft in approach.…”
mentioning
confidence: 95%